1997
DOI: 10.1063/1.474263
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer dynamics in the first excited singlet state of malonaldehyde

Abstract: Rotation-tunneling analysis of the origin band in the tropolone π*←π absorption system Semiclassical molecular dynamics simulations of excited state double-proton transfer in 7-azaindole dimers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…69 A smaller splitting in the 1 n* state, as compared to S o , [70][71][72] confirms the computational finding of a higher barrier in this excited state, ͑although later work questioned this interpretation͒. 73 Other experimental measurements are consistent with our computational finding that the 1 n* state of malonaldehyde is lower than 1 n*. 70,72 While there is no information on the asymmetric glyoxalmonohydrazine molecule itself, there are a number of studies of larger systems that contain the OH¯N intramolecular interaction within the context of one or more aromatic rings.…”
Section: Comparison With Past Worksupporting
confidence: 61%
“…69 A smaller splitting in the 1 n* state, as compared to S o , [70][71][72] confirms the computational finding of a higher barrier in this excited state, ͑although later work questioned this interpretation͒. 73 Other experimental measurements are consistent with our computational finding that the 1 n* state of malonaldehyde is lower than 1 n*. 70,72 While there is no information on the asymmetric glyoxalmonohydrazine molecule itself, there are a number of studies of larger systems that contain the OH¯N intramolecular interaction within the context of one or more aromatic rings.…”
Section: Comparison With Past Worksupporting
confidence: 61%
“…No evidence for the presence of resolved spectral tunneling doublets was reported by Firth et al [17] for Ar-isolated MA or by Chiavassa et al [18] Figure 1.2 Infrared spectrum of MA(OH) in the 200-300 cm -1 region due to Smith et al [15]. Spectral doublet separations DS 21 and DS 15 replace the single-peak assignments m 15 = peak 20 and m 21 = peak 26. in Ar, Kr, and Xe matrices. Smith et al [15] proposed a vibrational assignment for MA on the basis of their IR spectra for H and D isotopomers, comparative spectra for other substances, and a valence force field.…”
Section: Coherent Tunneling Splitting Phenomena In Malonaldehydementioning
confidence: 99%
“…Seliskar and Hoffman [20] reported vibronic spectral structure for the weakà A 1 B 1 ‹X X 1 A 1 (p*-n) [S 1 ‹S 0 ] absorption near 354 nm to have a spectral doublet separation (DS) of 7 cm -1 . Arias et al [21] applied the absorbance-based degenerate four-wave mixing (DFWM) spectroscopic method to the S 1 ‹ S 0 transition. With higher intrinsic spectral resolution, and spectral clarification arising through the reduction of signal due to hot band transitions that is inherent in this nonlinear spectroscopic technique, they found DS = |D 0 S 1 -D 0 S 0 |~19 cm -1 , to place the ffi 1 [21].…”
Section: Coherent Tunneling Splitting Phenomena In Malonaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26] Most theoretical studies have focused on tunneling splitting in the ground state, [27][28][29][30][31][32][33][34][35][36][37] but proton transfer in electronically excited states has also been studied. [38][39][40][41][42][43][44] Spectroscopic studies of the real-time dynamics of proton transfer have been limited, to our knowledge, to excited electronic states. [45][46][47] In an application to o-hydroxybenzaldehyde and related compounds, Lochbrunner et al demonstrated the utility of pump-probe photoelectron spectroscopy for probing the dynamics of intramolecular proton transfer in excited states.…”
Section: Introductionmentioning
confidence: 99%